Cholinergic autoantibodies from primary Sjögren's syndrome inhibit mucin production via phospholipase C and cyclooxygenase-2 in the rat submandibular gland - Daniela Passafaro; Leonor Sterin-Borda; Silvia Reina; Enri Borda (Wolters Kluwer Medknow Publications, 2011)
Background: Patients with primary Sjögren's syndrome (pSS) produce functional IgG against cholinoreceptor of exocrine glands modifying their activity. The aim of the present work was to demonstrate pSS IgG antibodies (pSS IgG) interacting with M 3 muscarinic acetylcholine receptors (mAChR) of rats submandibular glands that alter mucin release and production via phospholipase C (PLC) and cyclooxigenase-2 (COX-2) pathways. Methods:Mucin release and production of prostaglandin E2 (PGE2), and total inositol phosphates (InsP) were measured in rat submandibular gland in the presence of pSS IgG auto antibodies. Results: The auto antibodies interacting with M3 mAChR decreased mucin release and production through stimulation of PLC and COX-2. This stimulation leads to an incremental increase in InsP production and in PGE2 generation, inducing signalling through the prostaglandin membrane receptors subtype 2 (EP2). Moreover, the decrease in mucin production had negative correlation with PGE 2 generation and InsP accumulation. Conclusion: IgG in patients with pSS could play an important role in the pathoetiology of dry mouth, decreasing the salivary mucin through the production of proinflammatory substances and leading to the reduction in the protection of the oral tissues.